Complications of gastroesophageal reflux disease: 10-year experience: Zapleti gastroezofagealne refluksne bolezni: 10-letne izkušnje - Hojski, Aljaž; Crnjac, Barbara; Vuletić, Filip; Crnjac, Anton (Acta Medico-Biotechnica, 2021)
Purpose: Gastroesophageal reflux disease (GERD) is a common condition of modern times resulting from chronic reflux of gastric contents into the esophagus. The cause underlying GERD involves an imbalance between noxious and protective factors of the esophageal mucosa and a functional disorder of the lower esophageal sphincter (LES). The transitional release of the LES appearing more frequently and longer than physiologically normal is the main cause for the development of GERD. The negative effects of reflux can increase by disturbed esophageal motility, which is unable to regularly clear the esophagus in esophageal motility disorders and disturbed gastric emptying in large hiatal hernias and peptic ulcers. Typical GERD symptoms include a burning sensation or pain behind the sternum, return of bitter or acidic gastric content into the esophagus, rare odynophagia and extraesophageal signs, such as non-cardiac chest pain, chronic cough, and hoarsenessMethods: A literature revue and a review of clinical cases over a 10-year span in the Department for Thoracic Surgery University Medical Centre Maribor.Results: The study was also drawn from 10 years of experience with surgical treatment of GERD and its complications. The treatment of reflux esophagitis and asthma as a GERD complication is not the domain of a surgeon. Surgical treatment is indicated in passage-blocking conditions and in cases in which GERD cannot be managed with medical therapy. In the period from 2006–2015 we performed 928 surgeries to remove and prevent GERD complications.Conclusion: Several possible complications of GERD are known, among which the development of Barret’s esophagus as a pre-malignant condition of the esophageal mucosa and the development of glandular carcinoma of distal esophagus are especially dangerous. Therefore, a precise diagnostic treatment is necessary when treating the underlying disease of patients as the clinical picture of GERD often resembles problems related to other thoracic pathologies.
Keywords: gastroesophageal reflux disease; reflux esophagitis; complications; diagnostic procedures; treatment